Comparison between two cohorts of adolescent mothers in Southeastern Brazil - Ribeiro, Eleonora RO; Barbieri, Marco A; Bettiol, Heloisa; Silva, Antônio AM da (Revista de Saúde Pública, 2000)
OBJECTIVE: To compare the prevalence of pregnancy among adolescents and analyze trends in some social and biological variables among two cohorts of adolescent mothers in Ribeirão Preto, Brazil, during 1978/79 and 1994. METHODS: Two cohorts of adolescent mothers were interviewed shortly after delivery, comprising 943 women in the first survey (1978/79) and 499 in the second (1994). Both surveys covered more than 98% of births in all childbirth clinics. Only singleton livebirths from adolescent mothers living in the municipality were included in the analysis. The Chi-square test was used for statistical analysis, with a 0.05 significance level. RESULTS: The percentage of adolescent mothers increased from 14.1% in 1978/79 to 17.5% in 1994 (p